2021
DOI: 10.1590/s1677-5538.ibju.2020.0839
|View full text |Cite
|
Sign up to set email alerts
|

Complete corporeal preservation clitoroplasty: new insights into feminizing genitoplasty

Abstract: Introduction: 46,XX Congenital adrenal hyperplasia (CAH) remains the fi rst cause of genital virilization and current surgical techniques aim to restore female aspect of genitalia while preserving dorsal neurovascular bundle but not at the expense of not preserving erectile tissue. We aim to report our experience with a new surgical technique for clitoroplasty, completely preserving corporeal bodies, neurovascular bundles without dismembering the clitoris, in four patients with over a year follow up. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These results may be attributed to a deep understanding of anatomy and function of the clitoral tissue, especially with respect to the neurovascular bundles, which allow for preservation of the organ. 20 Various techniques have been described to correct clitoromegaly. 21 Fernandez et al, have introduced a complete corporeal preservation clitoroplasty by sparing the corpora cavernosa erectile tissue of the clitoris without disassembling the clitoris and leaving the dorsal neurovascular bundle untouched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be attributed to a deep understanding of anatomy and function of the clitoral tissue, especially with respect to the neurovascular bundles, which allow for preservation of the organ. 20 Various techniques have been described to correct clitoromegaly. 21 Fernandez et al, have introduced a complete corporeal preservation clitoroplasty by sparing the corpora cavernosa erectile tissue of the clitoris without disassembling the clitoris and leaving the dorsal neurovascular bundle untouched.…”
Section: Discussionmentioning
confidence: 99%
“…21 Fernandez et al, have introduced a complete corporeal preservation clitoroplasty by sparing the corpora cavernosa erectile tissue of the clitoris without disassembling the clitoris and leaving the dorsal neurovascular bundle untouched. This procedure kept clitoral erections, sensitivity and vascularity to the clitoris unharmed 20 . In support of the data presented in this study, Jun et al, have shown that pediatric clitoral reconstruction in patients with congenital adrenal hyperplasia (CAH) yielded minimal perioperative complications in Seoul, Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also have reported the use of fullthickness skin, myocutaneous grafts, or peritoneal vaginoplasty with more extensive donor areas (10)(11)(12)(13). However, in these patients, the scars often became more visible, associated with contractures and deformities of abdominal skin.…”
Section: Compared To the Traditional Mcindoe Technique Which Ismentioning
confidence: 99%